1987
DOI: 10.1046/j.1537-2995.1987.27688071702.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a donor population in western Venezuela

Abstract: To determine the characteristics of blood donors in western Venezuela, we collected data from 1983 to 1985 on 31,320 volunteer donors at the Blood Bank of the State of Zulia in Maracaibo. Fifty-nine percent of the donors were blood group O, 30 percent were group A, 9 percent were group B, and 2 percent were group AB. Most of the donors (93%) were Rh positive. One percent of donors had positive reactions to hepatitis B surface antigen, 3.15 percent for syphilis, 1.43 percent for antibodies to Trypanosoma cruzi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…HBV and HDV prevalence rates in other ecological and cultural environments in the region (whether large cities or nearby rural communities) differ clearly from those described above (Table 2). Data obtained from such cities and rural areas in Bolivia, Peru, Venezuela, Colombia, and Brazil (Aguiar et al, 2001;Blitz-Dorfman et al, 1994;Cabezas et al, 1994;Castro, 2000;de Márquez et al, 1993;Figueiredo et al, 2000;León et al, 1999;Konomi et al, 1999;Ljunggren et al, 1985;Ponce et al, 1994;Pujol et al, 1994;Weir-Medina et al, 1987) show prevalence of HBV infection similar to what is commonly found in any region with low endemicity. In surveys performed among non-selected individuals from some large urban areas like Bogotá, Caracas, Maracaibo, or Cochabamba, anti-HBc prevalence was close to that recorded among the general population of Madrid (Consejería de Salud, Comunidad de Madrid, 1995).…”
Section: Hbv and Hdv Prevalence In The Regionmentioning
confidence: 79%
“…HBV and HDV prevalence rates in other ecological and cultural environments in the region (whether large cities or nearby rural communities) differ clearly from those described above (Table 2). Data obtained from such cities and rural areas in Bolivia, Peru, Venezuela, Colombia, and Brazil (Aguiar et al, 2001;Blitz-Dorfman et al, 1994;Cabezas et al, 1994;Castro, 2000;de Márquez et al, 1993;Figueiredo et al, 2000;León et al, 1999;Konomi et al, 1999;Ljunggren et al, 1985;Ponce et al, 1994;Pujol et al, 1994;Weir-Medina et al, 1987) show prevalence of HBV infection similar to what is commonly found in any region with low endemicity. In surveys performed among non-selected individuals from some large urban areas like Bogotá, Caracas, Maracaibo, or Cochabamba, anti-HBc prevalence was close to that recorded among the general population of Madrid (Consejería de Salud, Comunidad de Madrid, 1995).…”
Section: Hbv and Hdv Prevalence In The Regionmentioning
confidence: 79%